2015
DOI: 10.1111/cars.12078
|View full text |Cite
|
Sign up to set email alerts
|

Home Care Workers’ Skills in the Context of Task Shifting: Complexities in Care Work

Abstract: Task shifting, which involves the transfer of care work from regulated health-care professionals to home care workers (HCWs), is a strategy to ensure the efficient delivery of home care services in Canada and internationally. Using a feminist political economy approach, this paper explores the effects of task shifting on HCWs' skills. Task shifting may be understood as a form of downward substitution-and an effort to increase control over workers while minimizing costs-as some of health-care professionals' res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…In Ontario, there are four main routes to become a formally educated PSW, including (1) the public college system, (2) the private career college system, (3) adult or continuing education programmes offered through public or separate school boards, and (4) non‐profit training organisations (Barken et al., ; HPRAC, , Personal Support Network of Ontario, ). In 2014, in an effort to standardise the education of PSWs in Ontario, the Ministry of Training, Colleges and Universities released the Personal Support Worker Program Standard and required all programmes to update and submit a curriculum for approval (Kelly & Bourgeault, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ontario, there are four main routes to become a formally educated PSW, including (1) the public college system, (2) the private career college system, (3) adult or continuing education programmes offered through public or separate school boards, and (4) non‐profit training organisations (Barken et al., ; HPRAC, , Personal Support Network of Ontario, ). In 2014, in an effort to standardise the education of PSWs in Ontario, the Ministry of Training, Colleges and Universities released the Personal Support Worker Program Standard and required all programmes to update and submit a curriculum for approval (Kelly & Bourgeault, ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to growing demand for home and community‐based services and to address shortages of professional staff and rising healthcare system costs, the PSW role has expanded to include care activities previously performed by RHPs (Barken et al., ; Berta et al., ; De Vliegher, Declercq, Aertgeerts, & Moons, ). This transfer of more advanced care activities to PSWs has been labelled “task‐shifting” in the literature (Barken et al., ; Denton et al., ; Zeytinoglu et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first review to explore how observational research can inform our understanding of the experiences and quality of care delivered by home‐care workers. While qualitative interviews and focus group methods have been used frequently to study home care (Barken, Denton, Plenderleith, Zeytinoglu, & Brookman, ; Lovelock & Martin, ; Yeh, Samsi, Vandrevala, & Manthorpe, ), methods of observation have to date been used less widely. From the studies we reviewed, the researchers observed various home‐care practices that were in line with good‐quality care, defined as care that was consistent, and enabled the development of trusting relationships between the home‐care providers and recipients (Cabana & Jee, ; Denton et al, ; Olsson & Ingvad, ; Saultz & Lochner, ).…”
Section: Discussionmentioning
confidence: 99%
“…As the demand for home care increases, due to cost and health human resource constraints more patient care is being transferred to UCPs resulting in a shift in UCP roles from traditional supportive care to more complex care activities (Tourangeau, Saari, & Patterson, ). This trend in the provision of home care has been referred to as task shifting (Barken, Denton, Plenderleith, & Zeytinoglu, ; Denton, Brookman, Zeytinoglu, Plenderleith, & Barken, ).…”
Section: Introductionmentioning
confidence: 99%